“Dosis de micronutrientes granulados en el cultivo de cebolla china (allium fistolosum) VAR. Roja chiclayana, en la provincia de Lamas” - Ramirez Sánchez, Franco Alexis (2014)
The present study was conducted in Fundo "The Pacific" Eng. Jorge Luis Pelaez Rivera, district Lamas, the effect of micronutrients (Micromate calciuum fortifieed) in relation to the development and production in growing Chinese onion was determined (Allium fistolosum L.), as well as decreasing the pollution of soil, water and air, which significantly extends the economic life thereof and profitability of the property. The study revealed that there are indeed of granular micronutrients (Ca, Mg, S, Zn, Fe, Mn, B, Cu Micromate fortifieed calcium) under agro-ecological conditions in the province of Lamas, and could also be demonstrated that increasing doses applications granular micronutrients (MCF) have described a positive linear effect on the variables of plant length, plant weight and performance. We worked with six (06) treatments at different application rates, with two witnesses (T01 manure posture and T02 absolute control), work group contained research of field development and crop management with their respective doses application was finally determined that the production system MICROMATE CALCIUUM FORTIFIEED is technically feasible and economically viable. Getting performance 62587.5 kg ha-1 with respect to the controls (T01 and T02) which underperformed the other treatment weighing 49.850,0 kg ha-1 and 44.712,5 kg ha -1. Keywords: Micromate calciuum fortified, Onion China, field, treatments, Performance, manure posture.